The Rat Race Between World Cities: In Search of Exceptional Places by Means of Super-Efficient Data Development Analysis - Karima Kourtit; Peter Nijkamp; Soushi Suzuki (Tinbergen Institute, 2013)
This paper aims to provide a new methodological and empirical contribution to the rising literature on the relative performance and benchmarking of large cities in a competitive world. On the basis of a recent detailed database on many achievement criteria of 35 major cities in the world, it seeks to arrive at a relative performance ranking of these cities by using Data Envelopment Analysis (DEA). A novel element is the use of a new type of `Super-Efficiency DEA' to identify unambiguously the high performers ('exceptional places') in the group of world cities investigated. This new productivity-based approach is complemented with two new directions in DEA research, viz. a Distance Friction Method and a Context-Dependent method.
Keywords: C8; O1; 330; world cities; city performance; Data Envelopment Analysis